PENGEMBANGAN BUKU CERITA MATEMATIKA UNTUK ANAK KELOMPOK B DI TK NEGERI PEMBINA INDRALAYA SELATAN - Ria Rosidah; Syafdaningsih syafar; sri sumarni (FKIP Universitas sriwijaya, 2017)
Research development has a view to produce story books mathematics. The development of story books mathematics it uses combination model of rowntree and evaluation tessmer. Model of rowntree consists of three stages, in the planning, developmental stage and the evaluation. At the evaluation an evaluation formative presented by tessmer consisting of five stage, in the self evaluation, experts review, one-to-one evaluation, small group evaluation and field test. Using techniques data collection observation. From the experts review obtained the average score the assessment of the experts on the Book 1 of 3,90% (category very valid), Book 2 of 3,90% (category very valid), Book 3 of 3,90% (category very valid), Book 4 of 3,90% (category very valid). Phase one-to-one evaluation obtained the average observations children with Book 1 of 85% (category very good), Book 2 of 86% (category very good), Book 3 of 87% (category very good), and Book 4 of 86% (category very good). The small group evaluaion obtained the average observation on the Book 1 of 88% (category very good), Books 2 of 90% (category very good), Book 3 of 91% (category very good), and Book 4 of 92% (category very good). At the field for observation test scores on the Book 1 of 95% (category very good), Books 2 of 95% (category very good), Book 3 of 91% (category very good), Books 4 of 95% (category very good). Of all stages already done so it can be concluded that story books mathematics expressed valid, practical, and have an effect potential for children.